The paying guests ebook - Waters, Sarah (2014)
The New York Times bestselling novel that has been called “a tour de force” ( Wall Street Journal) , “unputdownable” ( The Washington Post ), “a delicious hothouse of a novel” ( USA Today ), “effortless” ( The Economist ), “seductive” ( Vanity Fair ) and “pitch perfect” ( Salon )   “Superb, bewitching…Forget about Fifty Shades of Grey ; this novel is one of the most sensual you will ever read, and all without sacrificing either good taste or a "G" rating” – NPR   “One of the year’s most engrossing and suspenseful novels…a love affair, a shocking murder, and a flawless ending … Will keep you sleepless for three nights straight and leave you grasping for another book that can sustain that high.” — Entertainment Weekly (A rating) “ Volcanically sexy, sizzingly smart, plenty bloody and just plain irresistible." —USA Today (4 stars) It is 1922, and London is tense. Ex-servicemen are disillusioned; the out-of-work and the hungry are demanding change. And in South London, in a genteel Camberwell villa—a large, silent house now bereft of brothers, husband, and even servants—life is about to be transformed as impoverished widow Mrs. Wray and her spinster daughter, Frances, are obliged to take in lodgers. With the arrival of Lilian and Leonard Barber, a modern young couple of the “clerk class,” the routines of the house will be shaken up in unexpected ways. Little do the Wrays know just how profoundly their new tenants will alter the course of Frances’s life—or, as passions mount and frustration gathers, how far-reaching, and how devastating, the disturbances will be. Short-listed for the Man Booker Prize three times, Sarah Waters has earned a reputation as one of our greatest writers of historical fiction, and here she has delivered again. A love story, a tension-filled crime story, and a beautifully atmospheric portrait of a fascinating time and place, The Paying Guests is Sarah Waters’s finest achievement yet.